Mitral Valve Surgical Treatment with Mini-Invasive Access (Five-Year Results) - Vasyl V. Fylypchuk; Vasyl V. Lazoryshynets (Ukrainian Journal of Cardiovascular Surgery, 2024)
In the world, minimally invasive mitral valve surgery (MIMVS) has a recognized role in the surgical treatment of mitral valve (MV) diseases, however, this technique has not yet been widely used in our country. Due to the lack of clear clinical guidelines and recommendations in the choice of access to MV, many cardiac surgery centers implement a minimally invasive technique insufficiently often, and this procedure is characterized by complex learning curve.The aim. To analyze the results of MV surgical treatment using a minimally invasive approach.Materials and methods. Between 2020 and 2024, surgical treatment of MV insufficiency through a right-sided minithoracotomy was performed in 34 patients aged 18 to 67 at the National Amosov Institute of Cardiovascular Surgery of the National Academy of Medical Sciences of Ukraine, forming the primary study group. The comparison group included 36 consecutive patients (aged 25 to 81) who underwent isolated MV insufficiency correction through the classic approach, i.e. median longitudinal sternotomy (between 2023 and 2024).Results. The studied groups did not differ in terms of echocardiographic parameters. It was established that blood loss in the operating room was significantly higher with median longitudinal sternotomy compared to minithoracotomy (268.06 ± 14.3 mL and 192.50 ± 12.1 mL, respectively; p = 0.001). However, duration of operation and time of aortic compression were significantly longer in patients in the main group compared to controls, which is consistent with data from other researchers. Patients after minithoracotomy had a likely lower number of hours of analgesia, compared to those after median longitudinal sternotomy (88.35 ± 12.9 hours and 148.11 ± 16.6 hours, respectively; p = 0.009). Complications occurred less often in patients after minithoracotomy than in controls (8.8% and 11.1%, respectively; p > 0.05).Conclusions. MIMVS was associated with less blood loss in the operative period and reduced the severity of early postoperative pain. The effectiveness of surgical treatment using MIMVS was 100%, while complications occurred less often than in controls.